Dosimetric comparison of AcurosTM BV with AAPM TG43 dose calculation formalism in breast interstitial high-dose-rate brachytherapy with the use of metal catheters - Sinnatamby, Mourougan; Nagarajan, Vivekanandan; Reddy, Sathyanarayana; Karunanidhi, Gunaseelan; Singhavajala, Vivekanandam (Journal of Contemporary Brachytherapy, 2015)
Purpose : Radiotherapy for breast cancer includes different techniques and methods. The purpose of this study is to compare dosimetric calculations using TG-43 dose formalism and Varian Acuros TM BV (GBBS) dose calculation algorithm for interstitial implant of breast using metal catheters in high-dose-rate (HDR) brachytherapy, using 192 Ir. Material and methods : Twenty patients who were considered for breast conservative surgery (BCS), underwent lumpectomy and axillary dissection. These patients received perioperative interstitial HDR brachytherapy as upfront boost using rigid metal implants. Whole breast irradiation was delivered TG-43 after a gap of two weeks. Standard brachytherapy dose calculation was done by dosimetry. This does not take into account tissue heterogeneity, attenuation and scatter in the metal applicator, and effects of patient boundary. Acuros TM BV is a Grid Based Boltzmann Solver code (GBBS), which takes into consideration all the above, was used to compute dosimetry and the two systems were compared. Results : Comparison of GBBS and TG-43 formalism on interstitial metal catheters shows difference in dose prescribed to CTV and other OARs. While the estimated dose to CTV was only marginally different with the two systems, there is a significant difference in estimated doses of starting from 4 to 53% in the mean value of all parameters analyzed. Conclusions : TG-43 algorithm seems to significantly overestimate the dose to various volumes of interest; GBBS based dose calculation algorithm has impact on CTV, heart, ipsilateral lung, heart, contralateral breast, skin, and ribs of the ipsilateral breast side; the prescription changes occurred due to effect of metal catheters, inhomogeneities, and scatter conditions.